Clinical Indications of Avipattikara Choorna an Experiential and Scientific View - Acharya G, Shripathi; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2024)
Choorna is a type of formulation in which plant products are mixed in a definite proportion and pulverized before its use. These are given in various disorders with good outcome. Triphala Choorna, Talisadi Choorna, Sitopaladi Choorna, Laghu Gangadhara Choorna, Gangadhara Choorna, Trikatu Choorna, Lavana Bhaskara Choorna, Hingwashtaka Choorna And Hingu Vachadi Choorna are few Choorna Yogas which are commonly used in the management of various disorders by Ayurveda physicians. Avipattikara choorna is one such preparation which is commonly used in GIT disorders and disorders associated with constipation. It has actions like Pittahara, Virechana, Shoolahara, and antispasmodic actions. It is commonly given in Amlapitta, Pittaja Shoola, Perinamashoola, , Annadrava Shoola, Arshas And Malabandha. The present paper highlights about the clinical indications of Avipattikara choorna in an experimental and scientific view.